THE ROLE OF NAPOSO NAULI BULUNG (NNB) TOWARD SECURITY DEVELOPMENT IN THE VILLAGE OF PANGGORENGAN - Kusor Kusor (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This study describes of the role of Naposo Nauli Bulung (NNB) toward development of security in the village of Panggorengan. The purpose of this study was to analysis of development of security by Naposo Nauli Bulung. This study will help village apparatus to handle of security delepovment in Panggorengan village. This study used descriptive method with a qualitative approach. The focus of this study was on security delepovment Naposo Nauli Bulung. Security is the second priority basic human need based on physiological needs in Maslow's hierarchy which must be fulfilled during his life, because with the fulfillment of a sense of security every individual can work optimally in his life. Naposo Nauli Bulung has society activities is developmet security in village area. Village Security is a social institution formed on the initiative of the local community which is facilitated by village officials so that this institution is a village institution managed by village officials. The findings of this study show that Naposo Nauli Bulung has contribution on security development in panggorengan village.